A New Approach to Analyzing Ecological Problems: Planetary Boundaries - Mehmet Ali Çelik (Coğrafya Dergisi)
This research analyzes the planetary boundaries framework, which is a new approach to political ecology. Planetary boundaries examine environmental issues and climate change in a social context. Unlike radical ecology movements, this approach does not examine the current social, political, and economic structure against the ontology of green nature. The planetary boundaries uses the doughnut scheme and suggests that 11 social problems can be solved if nine ecological risks are brought within safe zones. This framework was first introduced in 2009 and further developed in 2015 and 2019. According to the planetary boundaries concept, not all ecosystems face the same level of risk, and environmental issues need to be categorized and analyzed quantitatively. For example, while the limit of carbon dioxide emissions had been 350 ppm, it has currently reached 412 ppm. The safe zone, also called the ecological ceiling, has been exceeded. Another category is biodiversity loss. While the limit for biodiversity loss had been 10%, it has currently reached over 16%. Recent studies have shown the ecological ceilings to have also been exceeded with regard to the nitrogen and phosphorus cycles, land cover changes, and deforestation. The global ecological ceilings for ozone depletion, ocean acidification, and freshwater consumption have not yet been exceeded, but the level of risk is increasing.